2018
DOI: 10.1016/j.ygcen.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcription ontogeny of hypothalamic-pituitary-thyroid axis development in early-life stage fathead minnow and zebrafish

Abstract: The hypothalamic-pituitary-thyroid (HPT) axis is known to play a crucial role in the development of teleost fish. However, knowledge of endogenous transcription profiles of thyroid-related genes in developing teleosts remains fragmented. We selected two model teleost species, the fathead minnow (Pimephales promelas) and the zebrafish (Danio rerio), to compare the gene transcription ontogeny of the HPT axis. Control organisms were sampled at several time points during embryonic and larval development until 33 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 59 publications
(80 reference statements)
3
37
0
Order By: Relevance
“…A previous analysis identified a similar shift in T3/T4 ratio at 10-14 dpf, attributed to higher deiodinase activity (Chang, Wang et al 2012). Indeed, while expression of thyroglobulin remains relatively stable from 10-20 dpf, deiodinase 2 expression increases twofold (Vergauwen, Cavallin et al 2018). However, these patterns are difficult to perfectly correlate with our measurements, as dpf (used in these previous analyses) is a poor proxy for size and developmental stage (Parichy, Elizondo et al 2009, McMenamin, Chandless et al 2016.…”
Section: Bioavailability Of Th Shifts During Mid-larval Developmentsupporting
confidence: 53%
“…A previous analysis identified a similar shift in T3/T4 ratio at 10-14 dpf, attributed to higher deiodinase activity (Chang, Wang et al 2012). Indeed, while expression of thyroglobulin remains relatively stable from 10-20 dpf, deiodinase 2 expression increases twofold (Vergauwen, Cavallin et al 2018). However, these patterns are difficult to perfectly correlate with our measurements, as dpf (used in these previous analyses) is a poor proxy for size and developmental stage (Parichy, Elizondo et al 2009, McMenamin, Chandless et al 2016.…”
Section: Bioavailability Of Th Shifts During Mid-larval Developmentsupporting
confidence: 53%
“…A previous analysis identified a similar shift in T3/T4 ratio at 10 to 14 days post fertilization (dpf), attributed to higher deiodinase activity . Indeed, while expression of thyroglobulin remains relatively stable from 10 to 20 dpf, deiodinase 2 expression increases 2‐fold . However, these patterns are difficult to perfectly correlate with our measurements, as dpf (used in these previous analyses) is an unreliable proxy for development …”
Section: Resultssupporting
confidence: 57%
“…53 Indeed, while expression of thyroglobulin remains relatively stable from 10 to 20 dpf, deiodinase 2 expression increases 2-fold. 54 However, these patterns are difficult to perfectly correlate with our measurements, as dpf (used in these previous analyses) is an unreliable proxy for development. 21,55 Shifts in allometric trajectories of WT fish occur at 8 to 10 mm SL (Figures 2A,B and 3C,D).…”
Section: Bioavailability Of Th Shifts During Midlarval Developmentmentioning
confidence: 76%
“…In a previous study we showed a peak of dio1 as well as dio2 mRNA in 5 day old normally developing zebrafish (Vergauwen et al, 2018), which does not suggest dominance of either isoform at that time point. However, it has been previously suggested that Dio2 is the major contributor to TH activation in developing zebrafish embryos (Darras et al, 2015;Walpita et al, 2010).…”
Section: Linking In Chemico Data To In Vivo Datamentioning
confidence: 58%